Penerapan Digitalpreneurship pada UMKM Kelurahan Krobokan Semarang - Kusumawati, Diah Ayu; Dian Essa Nugrahini (Penerbit Goodwood, 2024)
Purpose: The purpose of this activity is to provide education regarding digital entrepreneurship to MSMEs to be better prepared to run their businesses effectively and maintain their sustainability. Methodology/approach: The Community Service Team is developing digital-based MSMEs (Digitalpreneurship) by increasing the digital skills of business owners/workers and providing socialization for the implementation of platform selection strategies as online marketing media. In addition, we conducted a questionnaire survey to determine the extent to which MSME practitioners were able to understand counseling and their desire to apply it to their business. Results/findings: The result of this activity is that most MSME owners in Krobokan Village have implemented digital-based businesses (digitalpreneurship). However, when applying digital entrepreneurship, business actors do not make optimal preparations, including digital skills and platform strategies. These two variables are among the basic needs to maintain the sustainability of digital-based businesses. Most MSMEs are self-taught while running digital businesses. After carrying out this service activity and based on the survey results, it was stated that MSME owners began to prepare for and correct deficiencies in carrying out digital entrepreneurship, especially in digital skills and platform strategies. Limitations: The limitation of this community service activity is that it only focuses on improving digital skills for platform management and does not provide training on promotional strategies specifically for digital media. Contribution: Counseling and training on digital skills and platform strategies in this community service activity can maintain the sustainability of MSMEs in Krobokan Village in the current digital era.